Estudo comparativo, aleatorizado, em dupla ocultação, de orlistat versus placebo , de eficácia e segurança, em doentes obesos com hipercolesterolemia ligiera a moderada - Castro, JJ (2010)
INTRODUCTION: Obesity is a chronic disease and a serious health problem that leads to increased prevalence of diabetes, hypertension, dyslipidemia and gallbladder disease. OBJECTIVE: To evaluate the efficacy of orlistat for weight loss and improved lipid profile compared to placebo in obese patients with hypercholesterolemia, treated over a period of 6 months. METHODOLOGY: In a 6-month, multicenter (10 centers in Portugal), double-blind, parallel, placebo-controlled study, 166 patients, aged 18-65 years, body mass index (BMI) > or = 27 kg/m2, LDL cholesterol > 155 mg/dl, were randomized to a reduced calorie diet (600 kcal/day deficit) plus orlistat three times a day or placebo. Exclusion criteria included triglycerides > 400 mg/dl, severe cardiovascular disease, uncontrolled hypertension, type 1 or 2 diabetes under pharmacological treatment, and gastrointestinal or pancreatic disease. RESULTS: The mean difference in weight from baseline was 5.9% (5.6 kg) in the orlistat group vs. 2.3% (2.2 kg) in the placebo group. In the orlistat group 49% of patients achieved 5-10% weight loss and 8.8% achieved > 10%. The orlistat group showed a significant reduction in total and LDL cholesterol, with similar changes for HDL in both treatment groups. The frequency of gastrointestinal adverse events was slightly higher in the orlistat group than in the placebo group, leading to discontinuation in 7 patients. CONCLUSION: Treatment with orlistat plus a reduced calorie diet for 6 months achieved significant reductions in weight, BMI and lipid parameters.